The Wampanoag - Weinstein, Laurie Lee. (New York : Chelsea House, 1989)
Examines the history, changing fortunes, and current situation of the Wampanoag Indians.
Includes index.
Bibliography: p. 90-91.
Keywords: Wampanoag Indians -- Social life and customs; Wampanoag Indians -- History; Wampanoag Indians -- Ethnic identity; Indians of North America -- New England -- Social life and customs; Indians of North America -- New England -- History; Indians of North America -- New England -- Ethnic identity; Wampanoag Indians; Indians of North America -- New England